REALIZAREA ŞI EVALUAREA UNUI ESEU ÎNTR-O LIMBĂ STRĂINĂ - USM ADMIN (Moldova State University, 2007)
The article begins with presenting different points of view upon the essay written in a foreign language. Then, there is a short presentation of the manner of the essay writing during the centuries. One can read the characteristics of an essay and the elements that differentiate the essay from other literary pieces of work. There are shown the specific features and the structure of the following kinds of essay: the narative, the descriptive, the informative and the expositive essay.